Kosel, neue Informationen zu einem altbekannten wikingerzeitlichen Bestattungsort: Bioarchäologische Analysen der menschlichen Skelettreste aus Kosel-Ost - Palmowski, Valerie Elena (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
between the landscapes of Angeln and Schwansen. In the Viking Age it was part of the border region between the Saxonian and the Slavic cultures in the South and the Scandinavian culture in the North. In the context of a project supported by the Deutsche Forschungsgemeinschaft, ›Frühgeschichtliche und mittelalterliche Besiedlung von Angeln und Schwansen‹, two Viking Age settlements (9th/10th century) and a burial site (c. 930 – 975 AD) have been excavated between 1983 and 1993. In 2019, the author carried out the first analysis of the highly fragmented human skeletal remains from the burial site of Kosel- Ost for her dissertation project within the SFB 1070 RessourcenKulturen, project B 06. The following article summarises the first results: in Kosel-Ost both men and women, as well as children and adults were buried. Based on the archaeological record few child burials had been identified but could now be complemented with additional cases. An evaluation and contextual classification of individual burials, based solely on the archaeological data, is complex for Kosel-Ost. The consideration of singular aspects, such as the presence or absence of burial mounds, is not sufficient, to approach the complex burial reality. A bioarchaeological approach that combines archaeological and osteological data offers new perspectives. An assessment of dental pathologies revealed that varying dietary habits regarding carbohydrate enriched foods possibly existed. This was demonstrated by the occurrence of dental caries which is limited to and significantly correlates with individuals buried under burial mounds. Furthermore, differences in burial customs were re-evaluated on the basis of the osteological results.